The evolving field of kinase inhibitors in thyroid cancer. Issue 1 (January 2015) - Marotta, V.; Sciammarella, C.; Vitale, M.; Colao, A.; Faggiano, A.
Highlights Genes with kinase activity are implicated in the pathogenesis of thyroid cancer. This provides the rationale for using KIs. KIs are the most suitable treatment for RAI-refractory DTC. To date, only sorafenib has been approved for this indication. Vandetanib and cabozantinib have been approved for advanced MTC, but their toxicity suggests a selective use. KIs did not impact on clinics of ATC.